Brazil’s Cattle Sector Played Large Role in Fires During 2020 Moratorium - Schelly, Ian H.; Rausch, Lisa L.; Gibbs, Holly K. (Frontiers in Forests and Global Change, 2021)
In response to global concern about recent fires, Brazil placed a 120-day moratorium on burning in the Amazon in 2020. We assessed how the cattle sector was linked to these fires by estimating the number of cattle properties involved with fires despite the moratorium, and their roles in cattle supply chains. We examined the land cover prior to the fire to identify instances of fires associated with recent deforestation. Our results show that the cattle sector contributed disproportionately to the fires in 2020, in terms of both the number of properties involved and the area burned. Improvements in both supply chain policies and overall environmental governance in the Amazon are likely needed to avoid recurrences of the catastrophic scale of fires during the 2020 season.